2022
DOI: 10.3389/fmars.2022.853327
|View full text |Cite
|
Sign up to set email alerts
|

Blue and Red Light Color Combinations Can Enhance Certain Aspects of Digestive and Anabolic Performance in Juvenile Steelhead Trout Oncorhynchus mykiss

Abstract: The light spectrum varies with the altitude of the sun and shows different light colors in clear water. In this study, we aimed to investigate the response of juvenile steelhead trout Oncorhynchus mykiss (34.67 ± 2.69 g initial weight) under different light color conditions. The effects of different blue and red light combinations on plasma biochemical parameters, digestive enzyme activity, and RNA/DNA ratio were assessed in trout over 16 weeks. Six treatments were randomly assigned to 24 tanks with four repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Digestive enzyme activity is an important index for measuring fish digestion and metabolism ability (Perez-Sirkin et al, 2020;Yu et al, 2020a). This can be affected by feeding habits (Castro-Ruiz et al, 2019;Yu et al, 2020b) and light environment (Khanjani and Sharifinia, 2021;Chen et al, 2022a). In this study, activities of LPS and Trp in the stomach and midgut of juvenile steelhead trout were higher than those of AMS.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Digestive enzyme activity is an important index for measuring fish digestion and metabolism ability (Perez-Sirkin et al, 2020;Yu et al, 2020a). This can be affected by feeding habits (Castro-Ruiz et al, 2019;Yu et al, 2020b) and light environment (Khanjani and Sharifinia, 2021;Chen et al, 2022a). In this study, activities of LPS and Trp in the stomach and midgut of juvenile steelhead trout were higher than those of AMS.…”
Section: Discussionmentioning
confidence: 55%
“…Guller et al (2020) found that blue light could enhance the antioxidant capacity and immune performance of rainbow trout. Digestive enzymes are crucial for nutrient absorption and synthesis, and are also significantly influenced by light spectra and intensity in steelhead trout (Chen et al, 2022a) and Nile tilapia (Oreochromis niloticus) (Khanjani and Sharifinia, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the 3B9R and 6B6R environments' light colors both have a blue-redblue change, which might have led to the unique behavioral patterns observed in the mixed light groups. Previous research on the biochemical characteristics (Chen et al, 2022a) has found that fish in 3B9R and 6B6R environments showed myocardial stress with higher levels of lactate dehydrogenase (LDH). This physiological response may be correlated with the unique behavioral patterns of the mixed light groups.…”
Section: Discussionmentioning
confidence: 99%
“…Fish have evolved light-sensing mechanisms throughout their evolution to adapt to environmental light conditions, thereby lighting conditions affect fish behavior (Xu et al, 2019;Noureldin et al, 2021). Existing research has found that light spectrum conditions can influence the growth, immune response, and digestive and metabolic capabilities of steelhead trout (Chen et al, 2022a(Chen et al, , 2022b. Light affects fish metabolism, growth, and behavior through visual stimulation, and appropriate lighting conditions are beneficial for improving fish welfare and promoting growth (Ruchin, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation